IEEE Symposium on Human Centric Computing Languages and Environments, 2003. Proceedings. 2003
DOI: 10.1109/hcc.2003.1260197
|View full text |Cite
|
Sign up to set email alerts
|

Strategies and behaviors of end-user programmers with interactive fault localization

Abstract: End-user programmers are writing an unprecedented number of programs, due in large part to the significant effort put forth to bring programming power to end users. Unfortunately, this effort has not been supplemented by a comparable effort to increase the correctness of these often faulty programs. To address this need, we have been working towards bringing fault localization techniques to end users. In order to understand how end users are affected by and interact with such techniques, we conducted a think-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 21 publications
(21 reference statements)
0
27
0
Order By: Relevance
“…Second, the quick improvements-during even the first 10 user actionstreatment participants made to their classifiers suggest that users will remain engaged with Explanatory Debugging. This matters because research has shown that if an end-user debugging technique is not perceived as useful after a small number of interactions, users are unlikely to continue using it [32].…”
Section: Elucidebug's Explanations To End Usersmentioning
confidence: 99%
“…Second, the quick improvements-during even the first 10 user actionstreatment participants made to their classifiers suggest that users will remain engaged with Explanatory Debugging. This matters because research has shown that if an end-user debugging technique is not perceived as useful after a small number of interactions, users are unlikely to continue using it [32].…”
Section: Elucidebug's Explanations To End Usersmentioning
confidence: 99%
“…Prabhakararao and Ruthruff et al performed two human studies to gauge the effectiveness of an interactive fault localization tool developed for end users with little to no experience [21], [24]. The goal of their studies was to evaluate the use of feedback when locating faults and to generally study the process of fault localization, especially by users with no expert domain knowledge of the source.…”
Section: Related Workmentioning
confidence: 99%
“…Oftentimes, spreadsheets seeded with errors are used in empirical studies to evaluate the effectiveness or usability of errorprevention or -detection mechanisms [40], [41]. The seeding of errors is usually done manually on the basis of accepted classifications [7], [42].…”
Section: Introductionmentioning
confidence: 99%